Latin America on its path into the digital age : where are we? - Hilbert, Martin R. (ECLAC SantiagoCL)
Provides an inventory of the state of development with regard to the regional transition to the so-called Information Society, in order to untangle and structure present dynamics. Analyses the special characteristics of Latin America with regard to the integration of information and communication technologies. Identifies five fields of focus for inclusion into development theory viz. access, regulation framework, financing, education and the so-called soft factor (eWareness).